Analisis Pengelolaan Keuangan Dana Bantuan Operasional Sekolah (BOS): Studi Kasus Pada SMK Nurul Hikmah Tengguli Bangsri Jepara - Yanto Yanto; Anis Watin Izzah (Jurnal Rekognisi Akuntansi, 2018)
This study aims to analyze School Financial Management (Case Study of Nurul Hikmah Vocational High School). In the process of financial management at the Nuruh Hikmah Vocational School which includes planning and budget realization, it is suspected that it has not been fully carried out based on the principles of school financial management which includes fairness and efficiency. To find out the planning of preparation in the realization of the financial budget as well as the supporting and inhibiting factors for managing BOS funds at SMK Nurul Hikmah using qualitative research with a descriptive approach, collecting data using field techniques and literature with interviews. The results showed that school financial management at Nurul Hikmah Vocational School was also carried out. Planning for the management of BOS funds for the Nurul Hikmah Vocational School for the 2018-2019 school year began with the process of preparing the RKAS and preparing the RAB as well as implementing the use and finally doing bookkeeping. The supporting factor in implementing the program is collaboration between teacher staff. While the inhibiting factors in managing BOS funds are the amount of BOS funds that are not sufficient for school needs, delays in disbursing funds and difficulties in reporting the use of BOS funds due to lack of time and knowledge of the treasurer in financial management.